2015
DOI: 10.1007/s11120-015-0111-3
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of parallel-evolved cyanobacterium Synechocystis sp. PCC 6803 under acid stress

Abstract: Experimental evolution is a powerful tool for clarifying phenotypic and genotypic changes responsible for adaptive evolution. In this study, we isolated acid-adapted Synechocystis sp. PCC 6803 (Synechocystis 6803) strains to identify genes involved in acid tolerance. Synechocystis 6803 is rarely found in habitants with pH < 5.75. The parent (P) strain was cultured in BG-11 at pH 6.0. We gradually lowered the pH of the medium from pH 6.0 to pH 5.5 over 3 months. Our adapted cells could grow in acid stress condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…with an improved growth performance under acid stress at pH 5.5. A subsequent whole-genome sequence analysis suggested that SNPs in certain genes are involved in acid stress tolerance [ 136 ]. Similarity, heat-tolerant strains of Synechocystis sp.…”
Section: Adaptive Laboratory Evolutionmentioning
confidence: 99%
“…with an improved growth performance under acid stress at pH 5.5. A subsequent whole-genome sequence analysis suggested that SNPs in certain genes are involved in acid stress tolerance [ 136 ]. Similarity, heat-tolerant strains of Synechocystis sp.…”
Section: Adaptive Laboratory Evolutionmentioning
confidence: 99%
“…Recent genomic analysis of stress-evolved Synechocystis sp. PCC 6803 strains also revealed interesting information in adaptive evolution and stress response under high temperature or low pH [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, overall internal pH (the average of cytosol and thylakoid pH) across the same external pH range was only somewhat affected, suggesting that the observed limitation of energy supply might not be due to ΔpH alone. In support of the hypothesis that ATP supply might limit growth as pH is reduced, two strains of Synechocystis 6803 cells acclimated to pH 5.5 growth over 3 months independently acquired mutations in genes encoding F 1 –F 0 ATP synthase components ( Uchiyama et al, 2015 ), although these mutations are, as yet, functionally uncharacterized. Furthermore, experimental investigation of this hypothesis would require greater investigation of internal pH changes within the cell during photosynthesis and respiration, which to date has proven difficult ( Berry et al, 2005 ).…”
Section: Proposed Effects Of Environmental Ph On Ps II Mutantsmentioning
confidence: 99%